Water stress mitigation in vegetable cowpea through seed hardening and moisture conservation practices - S. Menon, Syama; Savithri, K.E. (Journal of Tropical Agriculture, 2015)
A field experiment was conducted at the College of Horticulture, Vellanikkara during summer season of 2014 (January - March) to study the potential benefits of seed hardening, antitranspirant spray and mulching for mitigating water stress in vegetable cowpea variety Kashi kanchan. Pod yield, stover yield as well as dry matter production were highest in plots irrigated at 2 days interval (farmer’s practice) followed by those irrigated at 5 days interval. Among treatments, plastic mulching recorded the highest pod yield (2.3 Mg ha-1) which was on par with plant residue mulching (2.1 Mg ha-1). Moreover, mulching resulted in an increased yield of 162-182% over control. Among the seed primers, 0.5% NaCl, and among the antitranspirants, lime water spray recorded the highest pod yield of 1.9 Mg ha-1 and 1.5 Mg ha-1respectively.